Machine Learning-Based Pain Intensity Estimation: Where Pattern Recognition Meets Chaos Theory—An Example Based on the BioVid Heat Pain Database - Peter Bellmann; Patrick Thiam; Hans A. Kestler; Friedhelm Schwenker (IEEE Access)
In general, classification tasks can differ significantly in their task complexity. For instance, image-based differentiation between vehicles and pedestrians is most likely expected to be less complex than CT-scan-based differentiation between several lung diseases. Intuitively, based on a human point of view, one can identify some classification tasks as more complex than other classification tasks. Moreover, based on expert knowledge and/or task-specific meta information, one could attempt to estimate the complexity ranks of specific classification tasks. In this work, based on the publicly available BioVid Heat Pain Database (BVDB), we experimentally confirm the intuitive assumption that the task of automated pain intensity recognition (PIR) is very challenging. Inspired by the field of chaos theory, we show that the BVDB-specific PIR task can not only be seen as highly complex, but is even identified as a classification task of chaotic nature. To this end, we apply Hao’s working definition for chaotic systems and provide an experiment-based chaos check method. To validate our approach, as a non-complex counterpart, we include a task of handwritten numerals distinction. Our study provides two main contributions, i.e.: i) an enhanced understanding for the still present and – more importantly – substantial gap between the ground truth and the predictions reported by different research groups in combination with automated PIR tasks; and ii) an approach for a numerical complexity check based on chaos theory. Different research directions are discussed for future work. Note that improving PIR accuracy performance is not part of the study objective.